2017
DOI: 10.1364/boe.8.004687
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantitative phase microscopy using programmable annular LED illumination

Abstract: Abstract:In this work, we present an efficient quantitative phase imaging (QPI) approach using programmable annular LED illumination. As a new type of coded light source, the LED array provides flexible illumination control for noninterferometric QPI based on a traditional microscopic configurations. The proposed method modulates the transfer function of system by changing the LED illumination pattern, which provides noise-robust response of transfer function and achieves twice resolution limit of objective NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…Quantitative phase imaging (QPI) [1,4] is one such technique that measures an incident field's phase shifts induced by the sample to recover the sample's physical properties without staining or labeling. Both interferometry [5][6][7][8] and non-interferometry based [9][10][11][12][13] QPI techniques have been developed to recover a sample's phase map in two-dimensions (2D). A single 2D integrated phase image, however, is insufficient for characterizing 3D heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative phase imaging (QPI) [1,4] is one such technique that measures an incident field's phase shifts induced by the sample to recover the sample's physical properties without staining or labeling. Both interferometry [5][6][7][8] and non-interferometry based [9][10][11][12][13] QPI techniques have been developed to recover a sample's phase map in two-dimensions (2D). A single 2D integrated phase image, however, is insufficient for characterizing 3D heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…fluorescence, DIC, phase contrast). More recently, it has been found that the shape of the illumination aperture has a significant impact on the lateral resolution and noise sensitivity of TIE reconstruction [160][161][162][163], and by simply replacing the conventional circular illumination aperture with an annular one, high-resolution low-noise phase imaging can be achieved by using only 3-plane intensity measurements [160,161]. Figure 18.…”
Section: Samplementioning
confidence: 99%
“…Quantitative phase imaging (QPI) 1,4 is one such technique that measures an incident field's phase shifts induced by the sample to recover the sample's physical properties without staining or labeling. Both interferometry [5][6][7][8] and intensity-only [9][10][11][12][13] QPI techniques have been developed to recover a sample's phase map in two dimensions. A single two-dimensional (2-D) integrated phase image, however, is insufficient for characterizing 3-D heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%